Reflexiones para la historia del quechuismo cachua - Ezcurra, Álvaro (2009)
The present article examines the history of the incorporation of the Quechua loanword “cachua” into Spanish. The “cachua”, a dance and song of Andean origin, was identified as idolatrous ever since its first appearance in documents of the 16th century and in the colonial Quechua lexicography. First, we offer a brief panorama of the contact between Quechua and Spanish in the colonial era and a text revision of historiographic, juridical and catechetical documentation, as well as of the old and contemporary lexicographical works in which the word is documented. Subsequently, we will concentrate on the incorporation of the loan at issue based on communicative, phonetic and semantic aspects.